The Phenomenon of Thrifting As An Alternative Solution Related to Reducing Environmental Impact on Fast Fashion - Rangga Timur Aryaputra; Tangguh Okta Wibowo; Rennardo Juan Stefan; Ruth Yusiana; Jessica (Formosa Journal of Multidisciplinary Research, 2023)
This study examines the impact of the fashion industry, in particular the fast fashion industry and the phenomenon of thrifting, on the environment and on society. Fast fashion, which responds to consumer demand for quick and affordable fashion trends, is environmentally damaging due to mass production using polluting materials and consumer demand. Alternatively, the phenomenon of thrifting, the practice of buying second-hand clothes, has the potential to mitigate the negative impacts of fast fashion by providing sustainable and affordable options. The method used by the researchers in this study is the phenomenological method to identify individual perspectives on a phenomenon that has happened or is happening to thrifting actors. Interviews with four informants, including users and sellers of second-hand clothes, revealed that they understand the concept of thrifting and the negative impact of clothing waste on the environment.